PENINGGALAN PRASEJARAH DI SEKITAR DI DANAU BUYAN-TAMBLINGAN DAN POTENSINYA SEBAGAI SUMBER BELAJAR SEJARAH DI ERA MILENIAL - I Wayan Pardi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
The purpose of writing this article is to identify the remains and lives of prehistoric people around Lake Buyan-Tamblingan, as well as to map the potential of these archaeological remains as a source of learning history in the Millennial Era. The findings show that around Lake Tamblingan found prehistoric remains, such as stone thrones, dolmens, menhirs, celak kontong lugeng luih, and statues of ancestors. The thing that attracts attention is the assumption or belief of the residents in the villages in the Lake Batur-Tamblingan area that these prehistoric/megalithic relics are still considered sacred and sacred, and it is proven that so-called Hindu temples in that area are actually a combination of holy places. megalithic/prehistoric with Balinese Hindu temples. The prehistoric relics around Lake Buyan-Tamblingan have enormous potential to be used as a source of history learning in the millennial era because these relics are able to visualize historical material which so far has only been narrated in textbooks.